ANALISIS KETERAMPILAN MENULIS PERMULAAN PESERTA DIDIK KELAS I SDN 5 SUNGAI RAYA - Mia Anggraini; Yunika Afryaningsih; Suriyana (STKIP Subang, 2025)
This study aims to decsribe the writing skilss of grade I students of SDN 5 Sungai Raya, which focuse on four indicators, namely (1) readabiliti of writing, (2) speed in writing, (3) accuracy of writing letters, and (4) accurate of how to hold pencil. The research methode used is qualitative methode, while the type of research used is descriptive. The research subjects were first grade student of DSN 5 Sungai Raya totaling 4 people, 2 boys and 2 girls. The techniques used in this research are test, observation, and documentation tehcniques, with test question sheets, observation guidelines, and analysis guidelines as research instruments. The result of the study indicate that the writing skilss of first grade students ats SDN 5 Sungai Raya are in the good category. The students’ writing s generaly legible, although there are still some errors such as incomplete letters, incorrect letters, and letters that are not in the correct position. Writing speed varies, with a time of 4 minutes and 47 seconds from the ideal standard of 5 minutes. In terms of letters accuracy, no reversed letters were found, although one student still frequently writes incomplete letters and three others make minor errors. Meanwhile, all students hold pencil using the correct technique, although one student positions their thumb too far from the pencil tip, and three students show the habit of pressing the pencil too hard, leaving marks on the paper.